الموظف الدبلوماسي في التشريع الليبي - الخوجة د. العارف صالح (Aljameai, 2025)
المستخلص: ينصب البحث بالأساس على الحيثية المهنية للموظف الدبلوماسي ذات الطبيعة المـــزدوجــة، فهــي داخـليـة اداريــاً وخــارجيـة دبلــومـــاسياً، يتـقرر لهــا جملـة مــن الـحقـوق بمقتضى أحكام القوانين المحلية والاتفاقيـات الدولية. فكان البحث بعنوان الموظف الدبلوماسي في التشريع الليبي مكون من مطلبين: أولهما لتبيان الطبيعة القانونية للوظيفة الدبلوماسية من خلال فرعين. وثانيهما اختص بحقوق الموظف الدبلوماسي من خلال فرعيين. قصور القانون الدبلوماسي المحلي عن النص على بعض الحقوق أهمها الحقوق التعبيرية وتلك المعنية بالمشاركة السياسية، ممّا يبرر الاستناد الى التشريعات الأخرى العامة أو الخاصة لممارسة تلك الاستحقاقات. Abstract: The research focuses mainly on the professional rationale of the diplomatic employee, which is of a dual nature, as it is internal administratively and external diplomatically, and a number of rights are determined under the provisions of domestic laws and international conventions. The research entitled "The Diplomatic Officer" in Libyan legislation consisted of two requirements: the first was to clarify the legal nature of the diplomatic function through two branches. The second concerned the rights of diplomatic agents through two branches. The inadequacy of domestic diplomatic law to provide for some rights, the most important of which are the rights of expression and those related to political participation, which justifies relying on other public or private legislation to exercise these entitlements.